(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Anita Desai (1937-) is unquestionably one of the mostcelebrated Indian –English writers. She is a prolific writer and has to hercredit a large number of creative works and a coherently growing readership.Anita Desai stands distinctive among her contemporaries in terms of IndianEnglish fiction. In her fiction she has denoted a psychological strand and inthe process she has projected a sensibility, which is generally not encounteredin other Indian Anglian Fictions. She depicts a significant literary dimensionby laying emphasis upon the exploration of inner climate, as well as the nuancesof sensibility. She explores all these aspects through her novels in a subtlemanner. As a novelist, Anita Desai designs the pattern of her novel to bringout the interior conflicts and dynamics within the human psyche. Her talent isexceptional in terms of the exploration of innate sensibility. The paper deals with the philosophical and psychologicalvision of Anita Desai. It throws light upon the basic themes incorporated inthe novel Where Shall We Go This Summer? (1975). She depicts a new dimension toEnglish fiction by laying emphasis upon the exploration of inner climate, theclimate of sensibility; a typical Indian phenomenon. It deals with the plightof Sita, the protagonist, whose consciousness flows through three consecutivestages of perception, memory and dream. Being a mother of four children, Sitais pregnant with her fifth child. This pregnancy shatters her severely and shedecides neither to give birth nor to undergo an abortive surgery, but to go tothe island of Manori, expecting miracles to happen there. She escapes to thisisland with a view to seeking solace and achieving the miracle of keeping thealready conceived child unborn. It presents an internal drama of Sita’swithdrawal from the stark realities of domestic life. The Paper also reflectsupon the inherent use of symbols, imagery, narrative style and language withinthe novel.